Association of Changes in Metabolic Syndrome Status With the Incidence of Thyroid Nodules: A Prospective Study in Chinese Adults - Liang, Qijun; Yu, Shouyi; Chen, Shihui; Yang, Yan; Li, Shuhua; Hu, Chenming; Huang, Danxuan; Kuang, Li; Li, Dongcai (Frontiers in Endocrinology, 2020)
Although several cross-sectional studies have shown an association of metabolic syndrome (MetS) with nodular thyroid disease, related prospective studies are scarce. This study investigated the association of MetS with thyroid nodule (TN) incidence in Chinese adults, and explored whether the development of or recovery from MetS is associated with changes in the risk of developing TNs. A total of 4749 Chinese aged 18-65 years were involved in this 6-year prospective study. The association of MetS with TN prevalence was examined. TN-free individuals at baseline (n=3133) were further examined. TN incidence rates in groups with different MetS statuses (MetS-free, MetS-developed, MetS-recovery and MetS-chronic) were analyzed. Of all participants, 18.21% and 31.65% had MetS and TNs, respectively. MetS patients had a higher TN prevalence than the non-MetS group (31.08% vs 19.81% in males, p<0.01; 59.52% vs 39.59% in females, p<0.01). Sex, age and MetS were independent risk factors for TNs. At a median follow up of 5.94 years, the MetS-chronic group (4.37/100 person-years) had a higher risk of TNs (adjusted incidence rate ratio [IRR]=1.288 [95%CI 1.014-1.636]) compared with the MetS-free group (2.72/100 person-years) in the whole cohort. In males, the MetS-chronic group (3.76/100 person-years) had a higher risk of TNs (adjusted IRR=1.367 [95%CI 1.017-1.835]) compared with the MetS-free group (2.31/100 person-years). In females, the risk of TNs was significantly higher in the MetS-chronic (6.44/100 person-years) and MetS-developed (6.31/100 person-years) groups compared with the MetS-free group (3.23/100 person-years).